2020
DOI: 10.1186/s12862-020-01657-w
|View full text |Cite
|
Sign up to set email alerts
|

Males of a sexually cannibalistic spider chemically assess relative female quality

Abstract: Background: Mate choice is a taxonomically widespread phenomenon, mostly exerted by females although male mate choice occurs as well. While costs and benefits of choosiness have been well studied, the underlying mechanisms are largely unclear. Different models exist, namely best-of-n or threshold rules, based on sequential or simultaneous sampling, which differ in the required cognitive demands. We applied an experimental approach to shed light on the underlying mechanisms of male mate choice in the sexually c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…As soon as a male P. mirabilis contacted silk of an adult female (unmated or mated), it emitted vibratory pulses at similar temporal patterns, dominant frequencies and pulse rates (Table 1). Thus, at the early stage of encounter as simulated in our experiments, when a male initiates courtship, male mate choice discriminates against immature and presumably also against heterospecific females, and male choice related to female condition and quality might take place later upon the physical encounter between the sexes or even after the first mating, as reported for Argiope bruennichi , where males exhibited choosiness only after the first copulation had taken place (Cory & Schneider, 2020).…”
Section: Discussionmentioning
confidence: 56%
“…As soon as a male P. mirabilis contacted silk of an adult female (unmated or mated), it emitted vibratory pulses at similar temporal patterns, dominant frequencies and pulse rates (Table 1). Thus, at the early stage of encounter as simulated in our experiments, when a male initiates courtship, male mate choice discriminates against immature and presumably also against heterospecific females, and male choice related to female condition and quality might take place later upon the physical encounter between the sexes or even after the first mating, as reported for Argiope bruennichi , where males exhibited choosiness only after the first copulation had taken place (Cory & Schneider, 2020).…”
Section: Discussionmentioning
confidence: 56%
“…Behavioural studies have shown that males adjust their mating tactic, i.e. whether they invest maximally in one female or seek to obtain a second mating with another female, according to female condition [ 41 , 42 , 68 ]. In spiders, as in other arthropods, female body mass correlates with fecundity [ 69 ] and in female A. bruennichi , body mass is positively correlated with age.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioural experiments with A. bruennichi revealed that males use chemical cues from female body surface and silk to both detect their presence and assess their mating status and body mass [39][40][41]. Moreover, field observations [42] and laboratory experiments [41] demonstrated that males are more likely to monopolize a female when she is relatively heavy and old, and older females attract more males than young ones in the field [43]. Although male mate choice has been well-studied in several spiders including A. bruennichi [20], the female perspective has rarely been looked at.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of the potential group (adults) to non-potential individuals was almost one and a half (1.5P:1NP). Age and sexual maturity of spiders may provide a broad range of mate choice decisions for males, as males of a sexually cannibalistic spider chemically assess relative female quality and mate with adaptive females (Cory & Schneider 2020).…”
Section: Resultsmentioning
confidence: 99%